METHODOLOGICAL FOUNDATIONS IN LEARNING FOREIGN LANGUAGE (Konferensiyalar | Conferences, 2024)
This article explores the methodological foundations in learning foreign languages, focusing on key approaches and practices that contribute to effective language education. Through a comprehensive literature review and analysis of dominant methodologies such as Communicative Language Teaching (CLT) and Task-Based Language Teaching (TBLT), the study highlights the importance of communicative competence and learner engagement in language instruction. Additionally, the integration of technology, cultural competence, and innovative pedagogical approaches like Content and Language Integrated Learning (CLIL) and Project-Based Learning (PBL) are discussed to enhance language acquisition and proficiency. The article emphasizes the significance of continuous professional development, collaboration among stakeholders, and research-based evaluations to optimize language education outcomes.